Glucosinolates and Omega-3 Fatty Acids from Mustard Seeds: Phytochemistry and Pharmacology - Gitishree Das; Ourlad Alzeus G. Tantengco; Rosa Tundis; Joyce Ann H. Robles; Monica Rosa Loizzo; Han Seung Shin; Jayanta Kumar Patra (Plants, 2022)
Seeds from mustard (genera Brassica spp. and Sinapsis spp.), are known as a rich source of glucosinolates and omega-3 fatty acids. These compounds are widely known for their health benefits that include reducing inflammation and lowering the risk of cardiovascular diseases and cancer. This review presented a synthesis of published literature from Google Scholar, PubMed, Scopus, Sci Finder, and Web of Science regarding the different glucosinolates and omega-3 fatty acids isolated from mustard seeds. We presented an overview of extraction, isolation, purification, and structure elucidation of glucosinolates from the seeds of mustard plants. Moreover, we presented a compilation of in vitro, in vivo, and clinical studies showing the potential health benefits of glucosinolates and omega-3 fatty acids. Previous studies showed that glucosinolates have antimicrobial, antipain, and anticancer properties while omega-3 fatty acids are useful for their pharmacologic effects against sleep disorders, anxiety, cerebrovascular disease, neurodegenerative disease, hypercholesterolemia, and diabetes. Further studies are needed to investigate other naturally occurring glucosinolates and omega-3 fatty acids, improve and standardize the extraction and isolation methods from mustard seeds, and obtain more clinical evidence on the pharmacological applications of glucosinolates and omega-3 fatty acids from mustard seeds.